Biological function and research progress of N6-methyladenosine binding protein heterogeneous nuclear ribonucleoprotein A2B1 in human cancers - Wu, Yue; Li, An; Chen, Can; Fang, Zhang; Chen, Lujun; Zheng, Xiao (Frontiers in Oncology, 2023)
N6-methyladenosine (m6A) is the most prevalent internal modification found in both mRNA and lncRNA. It exerts reversible regulation over RNA function and affects RNA processing and metabolism in various diseases, especially tumors. The m6A binding protein, hnRNPA2B1, is extensively studied as a member of the heterogeneous nuclear ribonucleoprotein (hnRNP) protein family. It is frequently dysregulated and holds significant importance in multiple types of tumors. By recognizing m6A sites for variable splicing, maintaining RNA stability, and regulating translation and transport, hnRNPA2B1 plays a vital role in various aspects of tumor development, metabolism, and regulation of the immune microenvironment. In this review, we summarized the latest research on the functional roles and underlying molecular mechanisms of hnRNPA2B1. Moreover, we discussed its potential as a target for tumor therapy.